Acrylic bone cements: Effects of the poly(methyl methacrylate) powder size and chitosan addition on their properties. Issue 3 (7th September 2013) - Endogan, Tugba; Kiziltay, Aysel; Kose, Gamze Torun; Comunoglu, Nil; Beyzadeoglu, Tahsin; Hasirci, Nesrin
ABSTRACT The effect of the particle size of poly(methyl methacrylate) (PMMA) and the incorporation of chitosan (CH) on the mechanical and thermal properties and the biocompatibility of acrylic bone cements were investigated. Three groups of bone cements were prepared with different PMMA particles. Groups 1 (BC1) and 2 (BC2) contained ground and sieved PMMA with particle sizes in the ranges 50–150 μm and 1–50 μm, and group 3 (BC3) contained synthesized PMMA microspheres with a size of about 1 μm. The mechanical properties of the three groups were similar, but their curing properties were significantly affected. The presence of CH improved the mechanical and thermal properties. For the BC1 group, the compressive strength increased more than 10 MPa, and the curing temperature decreased 12°. The cement having the optimum properties (BC1) was applied to rats, where it enhanced the bone bonding ability, and bioactivity was observed. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39662.